2009
DOI: 10.1111/j.1447-0756.2008.00961.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal complete heart block in pregnancy: Analysis of four cases and review of management

Abstract: When a multidisciplinary approach is used, both maternal and neonatal outcomes are good. The incidence of IUGR and preterm birth may be on the increase; hence, clinical vigilance for these conditions is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 6 publications
0
56
0
2
Order By: Relevance
“…No other complication like oligohydramnios or IUGR was seen in our case; however, Mandal et al [2] reported complications like IUGR (14 %), oligohydramnios (7 %), preterm labor (11 %) in the 21 patients studied. Suri et al [4] also reported IUGR in two out of the four cases studied with absent and reversed diastolic flow leading to a preterm delivery by cesarean section. There are different opinions regarding the need for pacemaker during pregnancy.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…No other complication like oligohydramnios or IUGR was seen in our case; however, Mandal et al [2] reported complications like IUGR (14 %), oligohydramnios (7 %), preterm labor (11 %) in the 21 patients studied. Suri et al [4] also reported IUGR in two out of the four cases studied with absent and reversed diastolic flow leading to a preterm delivery by cesarean section. There are different opinions regarding the need for pacemaker during pregnancy.…”
Section: Discussionmentioning
confidence: 97%
“…In most of these studies, the pregnant women were asymptomatic during pregnancy except for Mandal et al [2][3][4] who reported 21 pregnant women with complete heart block and found all of them to be symptomatic syncope and palpitation seen in 29 and 38 % women, respectively. CHB does not cause any specific pregnancy-related problems except for few cases of IUGR and preterm delivery [2,4]. The patient reported here also did not have any symptoms during the antenatal period, and no pregnancy-related complication was seen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4] Life-threatening arrhythmia is rarely reported in women with structurally normal hearts and few reports of atrioventricular block exist in the literature. 3,4 We present the case of a patient in her third trimester who developed non-sustained narrow and broad complex tachycardia (BCT) as well as transient ventricular standstill.…”
Section: Introductionmentioning
confidence: 99%